ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA BANK UMUM SYARIAH SEBELUM DAN SESUDAH MELAKUKAN SPIN-OFF (STUDI PADA BANK BTPN SYARIAH) - Zata Ghaisani Mazaya; Rulfah M Daud (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This study aims to determine whether there are differences in the performance of Public Islamic Bank (BTPN Syariah)  before  and  after  spin-off.  The  financial  ratios  used  are  CAR (Capital  Adequancy  Ratio),  NPF  (Non Performing Finance), FDR (Financing to Desposit Ratio), BOPO (Operating Expenses to Operating Income), and ROA (Return On Asset). The research method used in this research is descriptive comparative. Type of data used is secondary data in the form of quarterly financial statement of BTPN Syariah, quarter 1 2011 until with quarter 3 2014 for data before spin-off and quarter 4 2014 for data after spin-off. Data analysis was done by using Normality Test and Paired Sample T-Test. Data is processed by using SPSS (Statistical Pakage for Social Science) 25th version. The results of this study showed that at the ratios of BOPO there is no difference between before and after spin-off. While in the ratios of CAR, NPF, FDR and ROA there are difference between before and after spin-off